2015
DOI: 10.3889/oamjms.2015.039
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Noninvasive Imaging Techniques in Diagnosis of Carotid Plaque Morphology

Abstract: BACKGROUND:The stroke is leading cause of death and severe disability worldwide. Atherosclerosis is responsible for over 30% of all ischemic strokes. It has been recently discovered that plaque morphology may help predict the clinical behavior of carotid atherosclerosis and determine the risk of stroke. The noninvasive imaging techniques have been developed to evaluate the vascular wall in an attempt to identify “vulnerable plaques”.AIM:The purpose is to investigate the diagnostic accuracy of ultrasound, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…This finding corroborates with the work of Polak et al 18 Regarding comparison of two modalities in the evaluation of thrombosis, abnormality found were equal in both group. This finding corroborates with the finding of lukanova et al 19…”
Section: Discussionsupporting
confidence: 93%
“…This finding corroborates with the work of Polak et al 18 Regarding comparison of two modalities in the evaluation of thrombosis, abnormality found were equal in both group. This finding corroborates with the finding of lukanova et al 19…”
Section: Discussionsupporting
confidence: 93%
“…Last, we used ultrasound to assess the presence of plaque, which may be less reliable than the high-resolution magnetic resonance imaging (MRI) or computed tomography (CT). However, one study investigating the accuracy of ultrasound, CT, and MRI in diagnosis of carotid plaque morphology found that ultrasound has higher accuracy for diagnostics of carotid plaque morphology than CT or MRI 29 . In addition, compared with CT or MRI, ultrasound is safe, noninvasive, and inexpensive 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Carotid plaque was detected by ultrasonography examination which has been proved to have high sensitivity and speci city [12]. The measurement and assessment of CP have been described in detail previously [11].…”
Section: Carotid Ultrasonography Examinationmentioning
confidence: 99%